Faktor-Faktor Penghambat Pengembangan Pemasaran Melalui E-Katalog UMKM Berbahan Dasar Nanas Kota Prabumulih - Ermanovida; Aulia Utami Putri; Dwi Mirani; Sylvie Agustina; Zakiyah, Zakiyah (Wardah, 2024)
The national development of Indonesia involves the active participation of society, with the government serving as a guide and facilitator in achieving general welfare. One sector that is a focus of development is Micro, Small, and Medium Enterprises (MSMEs), which play a significant role in enhancing the economy, creating jobs, and supporting income distribution. In the city of Prabumulih, known for its pineapple potential, pineapple-based MSMEs are crucial to the local economy. However, MSME actors in Prabumulih face challenges in accessing digital marketing, particularly in utilizing government procurement platforms through E-Catalogs. Therefore, this study aims to identify the factors that hinder the development of marketing for pineapple-based MSMEs in Prabumulih through the E-Catalog system. Using a descriptive qualitative method and in-depth analysis, this research finds that a lack of guidance in digital marketing, limited access to information, and difficulties in meeting the formal requirements for e-purchasing are the main obstacles. This study recommends enhancing digital training, improving access to information, and providing technical assistance to MSME actors so they can adapt to the E-Catalog mechanism and thrive in the digital era.